DIGITAL LABOR DESDE LATIN AMERICA: A PLURIVERSAL LENS - Grohmann, Rafael; Hidalgo Cordero, Kruskaya; Martins, Helena; Posada, Julian; Salim Wagner, Camila (AoIR Selected Papers of Internet Research, 2026)
The progression of the gig or platform economy and the development of artificial intelligence in Latin America have led to the widespread adoption of computer-mediated forms of work as a means of income for many across the region. This panel examines instances of platform and AI-related work through the perspectives of theories that have been strongly developed within the region. The panel focuses on the study of platform-mediated data work and AI-related labor through the Brazilian concept of viração, the notion of extractivism, and regional conceptualizations of Participatory Action Research. Additional discussions explore feminist unionism in location-based platforms such as ride-hailing and delivery through the concept of biosindicalismo and Latin American decolonial and feminist thought, as well as the study of freelance platforms through the lens of the Brazilian political economy of communication.